A estrutura de metas de sala de aula e a motivação de alunos para aprender - Marques, Juliana Pelinsom (2009)
The study evaluates the motivation of students from elementary school on the basis of the achievement goals adopted and the classroom goal structure from the students perceptions and teachers descriptions of educational practices. The participants were 106 students from seventh and eighth grade (brazilian educational system), a Spanish Language, an Arts and a Health and Life Quality teachers. The students personal goals were evaluated by the Scale of Evaluation of the Motivation to Learning. The educational practices were described from the Scale of the Classroom Goal Structure filled by the students and from the answers provided by the teachers in an interview. The percentages of the students from the classes 1, 2, 3 and 4, who adopted adaptive patterns of achievement goal were, respectively, 19,2%, 36,0%, 29,4% e 20,0%; the percentages of students who adopted non-adaptive patterns were 46,2%, 44,0%, 52,9% e 45,0%. The students from Class 1 agreed partially that the tasks given by the teachers were motivating and the evaluation by the domain; students from other classes partially disagreed. The teachers described the use of diversified activities and the evaluation based on different procedures. It is concluded that the educational practices, even if they present some positive aspects, do not have the basic characteristics of the practices associated with the promotion of motivation to learn. It is discussed the contributions of the Achievement Goal Theory for the understanding of the motivation at school.